Monitoring Anticoagulant Therapy by Activated Partial Thromboplastin Time: Hirudin Assessment - Nurmohamed, Michael T; Berckmans, René J; Morriën-Salomons, Willy M; Berends, Fenny; Hommes, Daan W; Rijnierse, Joep J M M; Sturk, Augueste (Thrombosis and Haemostasis, 1994)
Background. Recombinant hirudin (RH) is a new anticoagulant for prophylaxis and treatment of venous and arterial thrombosis. To which extent the activated partial thromboplastin time (APTT) is suitable for monitoring of RH has not been properly evaluated. Recently, a capillary whole blood device was developed for bed-side monitoring of the APTT and it was demonstrated that this device was suitable to monitor heparin therapy. However, monitoring of RH was not evaluated.Study Objectives. To evaluate in vitro and ex vivo the responsiveness and reproducibility for hirudin monitoring of the whole blood monitor and of plasma APTT assays, which were performed with several reagents and two conventional coagulometers.Results. Large interindividual differences in hirudin responsiveness were noted in both the in vitro and the ex vivo experiments. The relationship between the APTT, expressed as clotting time or ratio of initial and prolonged APTT, and the hirudin concentration was nonlinear. A 1.5-fold increase of the clotting times was obtained at 150-200 ng/ml plasma. However, only a 2-fold increase was obtained at hirudin levels varying from 300 ng to more than 750 ng RH/ml plasma regardless of the assays. The relationship linearized upon logarithmic conversion of the ratio and the hirudin concentration. Disregarding the interindividual differences, and presuming full linearity of the relationship, all combinations were equally responsive to hirudin.Conclusions. All assays were equally responsive to hirudin. Levels up to 300 ng/ml plasma can be reliably estimated with each assay. The manual device may be preferable in situations where rapid availability of test results is necessary.